The Influence of Self-Efficacy and Learning Interest on the Mathematical Problem-Solving Ability of MAN 1 Bone Students - Hamzah Upu; Muhammad Ammar Naufal; Nur Anisa Syam; Obeng, Sharifah Nasriah Wan (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study investigates the effect of self-efficacy and learning interest on the mathematical problem-solving skills of tenth-grade students at MAN 1 Bone. Employing an ex post facto design, the research involved 80 students selected from a population of 356 through systematic random sampling. Data were collected using self-efficacy and learning interest questionnaires, along with a problem-solving test on three-variable linear equations. The data were analyzed through descriptive and inferential statistics using multiple linear regression analysis. The descriptive findings indicate that most students demonstrated moderate levels of self-efficacy, learning interest, and problem-solving ability. Inferential analysis revealed that both self-efficacy and learning interest significantly and positively affected problem-solving skills, individually and jointly. Self-efficacy accounted for 29.6% of the variance, learning interest contributed 22%, and their combined effect reached 51.6%. These results highlight the essential role of psychological and motivational factors in mathematical learning. Strengthening students’ confidence and interest can enhance their problem-solving competence, suggesting that instructional strategies should prioritize fostering both attributes to improve learning outcomes. This research contributes to the development of scientific insight, particularly in the field of education, related to self-efficacy, learning interest, and students' ability to solve mathematical problems. Furthermore, it can serve as a reference for implementing more effective learning models to increase students' learning interest.